SMALL BUSINESSES IS A SPHERE OF INNOVATION IN THE AGE OF GLOBALIZATION - Riapukhina, Viktoriia N.; Gennadyevna Romanovich, Liudmila; Alexeevna Romanovich, Marina; Vladimirovna Vybornova, Valentina (Journal of Applied Engineering Science, 2014)
The achievement of a sustainable growth and competitive of national growth is a cross-cutting theme, the success of it is determined the development of economic institutes and establishing of new competitive position. The maximum competitive becomes an economic in which knowledge and innovation are created, distributed and used effectively. Therefore, at the present stage of development of the world economic system transition to a knowledge economy is becoming one of the key elements of a national strategy to improve the country’s competitiveness in the international arena. The article considers actual questions of small innovation business development in modern terms - increase the global competition for the factors which determine the competitiveness of innovative systems, primarily for highly skilled labor force and the «smart» money (investments, which attracting projects in new knowledge, technologies, and competencies), a sharp increase in the mobility of these factors.